Satisfaction As A Mediator In The Relationship Between Service Quality And Facilities To Student Loyalty - Danil Pratama Putra; Zulganef Zulganef (UNIVED Press, 2025)
The purpose of this study was to determine the role of satisfaction in mediating the relationship between services and facilities with student loyalty at the National University of the Republic of Indonesia. The research method uses a quantitative approach and the analysis techniques used are descriptive analysis and SEM-PLS analysis. The source of this study uses primary data. Data collection in this study used a questionnaire. The sample of this study was 100 people. Based on the results of the descriptive analysis, it can be seen that product quality, product price, consumer satisfaction and repeat purchase interest according to respondents are still in the sufficient category. Based on the test results, it shows that student satisfaction functions as a significant mediator between services and facilities and student loyalty. This means that good services and facilities will increase student satisfaction, which will ultimately strengthen their loyalty to the university.